PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI VARIABEL KEPUASAN PELANGGAN - Januar Habibi Mahsyar (Universitas Kuningan, 2020)
Abstract PT Pos Indonesia (Persero) as a State-Owned Enterprise (BUMN) which carries out the mission of postal mail and postal parcel courier services in Indonesia with premium products, Special Express Post is a delivery service with a maximum travel time of 4 days that reaches the recipient quickly, precise, safe and reach all parts of Indonesia. One strategy to foster customer satisfaction that leads to customer loyalty is the formation of a brand image and the best possible service quality in the minds of postal customers.The research method used in this research is descriptive verification with a quantitative approach, to determine the significant relationship between the variables of brand image, service quality to customer satisfaction and customer loyalty. The population in this study were customers of the Kuningan Post Office, users of special express mail delivery services, amounting to 1,769. Techniques and data sources were obtained from literature studies and questionnaires to 298 respondents who were designated as samples with a significance level of 5%.The results of the hypothesis test indicate that the variables of brand image and service quality partially have a positive and significant effect on customer satisfaction. Customer satisfaction variables partially have a positive and significant effect on customer loyalty. Brand image variables partially have a positive and significant effect on customer loyalty. Service quality variable partially does not have a significant effect on customer loyalty. Simultaneously, brand image and service quality have a positive effect on customer satisfaction and loyalty. Keywords: Brand Image; Service Quality, Customer Satisfaction, Customer Loyalty.